Процес великомасштабного складкоутворення в осадовому шарі земної кори - Лубков, М.В. (Геоінформатика, 2014)
На основі варіаційної скінченно-елементної методики для ортотропних в’язкопружних багатошарових оболонок, які перебувають в умовах квазістаціонарного навантаження, змодельовано процеси великомасштабного складкоутворення в осадовому шарі земної кори. Встановлено, що збільшення ступеня тріщинуватості осадових порід і відхилення стискувальних геотектонічних зусиль від горизонтального напрямку приводять до зниження швидкості росту складок. Процеси утворення антикліноріїв і синкліноріїв в осадовому шарі земної кори, а також швидкості цих процесів суттєво залежать від форм і розмірів площин зминання осадових порід. На основе вариационной конечно-элементной методики для ортотропных вязкоупругих многослойных оболочек, которые находятся в условиях квазистационарного нагружения, проведено моделирование процессов крупномасштабного складкообразования в осадочном слое земной коры. Установлено, что увеличение степени трещиноватости осадочных пород и отклонение сжимающих геотектонических усилий от горизонтального направления приводят к снижению скорости роста складок. Процессы образования антиклинориев и синклинориев в осадочном слое земной коры, а также скорости этих процессов существенно зависят от форм и размеров плоскостей смятия осадочных пород. Based on the finite element method of three dimensional visco-elastic variation in the orthotropic foliated shells proximity, where shells are in quasi stationary loading process, the authors carried out, modeling of large scale fold forming processes in the crust sedimentary layer. The presented method allows us to calculate heterogeneities of the considered geological structures of both geometrical and rheological character. As a result, it is found, that fold velocities growth and fold forms forming depend on sedimentary rocks fracturing degree and on the deviation of the constringent geotectonic forces from horizontal direction, as well as on forms and sizes of the sedimentary rocks contortion areas. Consequently, sedimentary rocks fracturing degree leads to decreasing of the folds growth velocities. Deviation of the constringent geotectonic forces from horizontal direction also leads to their decreasing. Anticlinoriums and synclinoriums forming processes, and also velocities of these processes greatly depend on forms and sizes of the sedimentary rocks contortion areas. Moreover, anticlinoriums forming process is typical for contortion areas of big sizes. As the contortion area size decreases in the direction of compressing forces to some characteristic value, anticlinorium growth velocity decreases to zero, and qualitative transition to synclinoriums forming process takes place. Besides, as the respective contortion area size decreases, synclinorium growth velocity increases from zero to some maximum value, and then decreases to zero. In the case of anticlinoriums forming, sedimentary contortion area sizes in transversal direction relatively to geotectonic forces action do not effectively influence the process velocity. But In the case of synclinoriums forming, sedimentary contortion area size shortening leads to decreasing of the process velocity. The obtained information can be used for orogeny processes explorations as well as large geostructures forming and changing processes.